2022
DOI: 10.3390/v14091909
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of Influenza Circulation in the Russian Federation during the Delta and Omicron COVID-19 Era

Abstract: Influenza circulation was substantially reduced after March 2020 in the European region and globally due to the wide introduction of non-pharmaceutical interventions (NPIs) against COVID-19. The virus, however, has been actively circulating in natural reservoirs. In summer 2021, NPIs were loosened in Russia, and influenza activity resumed shortly thereafter. Here, we summarize the epidemiological and virological data on the influenza epidemic in Russia in 2021–2022 obtained by the two National Influenza Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…17 The BA.1-and BA.5-induced interferon responses generated an antiviral state that protected infected cells from super-infection with influenza A viruses, showing that the Omicron-induced interferon response is of functional relevance. Our analysis of the spread of influenza-like illnesses during the Delta and BA.1 infection waves (Figure S6) and a number of additional studies [31][32][33][34][35] suggest that Omicron may interfere with influenza A virus transmission. However, these are correlations that need to be considered with care, and a causative relationship remains to be established.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…17 The BA.1-and BA.5-induced interferon responses generated an antiviral state that protected infected cells from super-infection with influenza A viruses, showing that the Omicron-induced interferon response is of functional relevance. Our analysis of the spread of influenza-like illnesses during the Delta and BA.1 infection waves (Figure S6) and a number of additional studies [31][32][33][34][35] suggest that Omicron may interfere with influenza A virus transmission. However, these are correlations that need to be considered with care, and a causative relationship remains to be established.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, three further studies reported a decrease of influenza A virus infections when the Delta variant was replaced by the Omicron variant. [31][32][33] Additional studies found that Omicron patients were less likely to be coinfected with influenza A viruses than Delta patients 34 and that an H3N2 outbreak in Brazil only occurred after a decline in Omicron cases. 35 Notably, such observations do not provide conclusive evidence on a potential impact of Omicron circulation on influenza A virus spread.…”
Section: The Ba1-induced Antiviral State Is Primarily Mediated Via Ty...mentioning
confidence: 98%
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…IBV, HBoV, and enteroviruses were the most common pathogens of viral coinfection. In previously published reports Influenza A virus was seen more frequently as a co-infectious agent with SARS-CoV-2 [ 63 ]. In our study, Influenza B virus was reported as a coinfection pathogen in 15 cases compared to zero with influenza A virus.…”
Section: Discussionmentioning
confidence: 99%